2008
DOI: 10.1021/ja0778500
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Bikunin Glycosaminoglycan

Abstract: The structure of an intact glycosaminoglycan (GAG) chain of the bikunin proteoglycan (PG) was analyzed using a combined top-down and bottom-up sequencing strategy. PGs are proteins with one or more linear, high-molecular weight, sulfated GAG polysaccharides O-linked to serine or threonine residues. GAGs are often responsible for the biological functions of PGs, and subtle variations in the GAG structure have pronounced physiological effects. Bikunin is a serine protease inhibitor found in human amniotic fluid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 58 publications
4
98
0
Order By: Relevance
“…Urine fraction 2 was found to contain un-, 4-, 6-, and disulfated CS disaccharides, whereas urine fraction 1 was found to contain un-and 4-sulfated CS disaccharides. The CS composition of purified I␣I from human plasma has been reported to contain un-and 4-sulfated disaccharides in a ratio of 3:1 (26,27). This is in agreement with fraction 1 analyzed in this study that was found to be the major population of bikunin in each of the fluids analyzed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Urine fraction 2 was found to contain un-, 4-, 6-, and disulfated CS disaccharides, whereas urine fraction 1 was found to contain un-and 4-sulfated CS disaccharides. The CS composition of purified I␣I from human plasma has been reported to contain un-and 4-sulfated disaccharides in a ratio of 3:1 (26,27). This is in agreement with fraction 1 analyzed in this study that was found to be the major population of bikunin in each of the fluids analyzed.…”
Section: Discussionsupporting
confidence: 89%
“…The CS chains of urinary bikunin and plasma I␣I have been found to contain 15 Ϯ 3 disaccharides of which ϳ5 disaccharides are 4-sulfated on GalNAc and clustered near the reducing end (23)(24)(25)(26)(27). The CS chain linkage region of bikunin in urine and plasma has been shown to contain a disulfated hexasaccharide (24,25) on its non-reducing end, whereas other groups have suggested that the non-reducing end is monosulfated on the GalNAc residue (9,28).…”
mentioning
confidence: 99%
“…The two HCs are positioned in close proximity, with HC2 toward the reducing end of the CS chain (8). The CS chain is 12-18 disaccharides long, and on average, every fourth disaccharide is sulfated (C-4-S) (8,9). The remaining disaccharides are unsulfated (C-0-S) (8,9).…”
mentioning
confidence: 99%
“…The bikunin proteins inter-␣-inhibitor (I␣I), pre-␣-inhibitor (P␣I), and HC2⅐bikunin contain the serine proteinase inhibitor bikunin, which is a member of the I2 Kunitz-BPTI inhibitor family (MEROPS data base) (5,6). Bikunin carries a single chondroitin sulfate (CS) chain originating from Ser-10 (7) composed of both unsulfated chondroitin and chondroitin 4-sulfate (8,9). Furthermore the bikunin proteins contain different heavy chains (HCs) selected from a group of five proteins (10), but only three of the five homologous HCs have been identified in complex with bikunin.…”
mentioning
confidence: 99%